EFEKTIVITAS FUNGSI PENDIDIKAN DAN REKAYASA LALULINTAS GUNA MENCEGAH KORBAN KECELAKAAN LALU LINTAS PADA ANAK-ANAK USIA SEKOLAH - Jais, Adhi; Saputra, Ebit Bimas (UNES Journal of Swara Justisia, 2018)
On the Elucidation of Law No. 22 of 2009 on Traffic and Road Transport states Education and traffic engineering is the responsibility of the Police. Some victims from laka then are children of school age. The nature of this research is descriptive research with normative juridical approach method as main approach and empirical juridical as supporting approach. The results showed the Function of Education and Traffic Engineering (Dikyasa Lantas) is one of the preventive efforts in tackling the problem in the field of traffic. Dikmas activities are carried out by providing knowledge on school traffic at the time of admission and introduction of the school. Various programs of introducing traffic rules to children are done with the aim of avoiding children from traffic accidents. Constraints faced are internal factors are still lack of facilities and infrastructure, lack of personnel who have the special ability to be educators or teachers. Externally constrained is the lack of public awareness of the importance of culturally and well-ordered culture in the street, lack of support from various parties to create security, safety, order and smooth road traffic, still lack of road infrastructure and infrastructure to support the safety of traffic. The effectiveness of the Education and Traffic Engineering Function (Dikyasa Lantas) is seen from the decrease of traffic accident with the victims of school age children in Padang Police Regencies